Study on the development characteristics and spatial and temporal patterns of population ageing in 31 central cities in China - Zhang, Le; Ren, Hengna; Li, Chen (Frontiers in Public Health, 2024)
Background Population ageing is inseparable from technological innovation, social progress and the development of human civilization, and constitutes a new element in the development of contemporary human history. Objective To dynamically analyses the developmental, structural and growth characteristics of population ageing in 31 provincial capitals and municipalities in China, using the data of the fifth national census in 2000 and the seventh national census in 2020. Methods The development characteristics and spatial and temporal patterns of population aging in the 31 cities were measured using the population aging index growth model, Theil’s index, coefficient of variation, population aging index and other analytical methods. Results (1) From 2000 to 2020, the population aging rate of the 31 central cities generally increased, and the population aging level of the cities showed the characteristics of “East-Central-Northeast-West” to “Northeast-East-Central-West” decreasing. (2) Regional differences in the ratio of old to young are relatively high, while regional differences in the level of population ageing are relatively small. The level of population ageing is classified with the indicators of size structure, family structure and age structure in the first and third quadrants, and with the geographic concentration rate in the second and fourth quadrants. (3) China’s population ageing has a T-shaped spatial distribution characteristic pointing along the coast - along the Yangtze Rivers. Conclusion The 31 central cities are the center of gravity of China’s economy and have strong economic power in dealing with the challenges of population ageing, but how to make population ageing compatible with the economy and society, and then promote sustainable population development, is a topic that needs further attention in the study.